Assessment of water sources and quality for livestock and farmers in the Rift Valley area of Ethiopia: Implications for health and food safety - Amenu, K. (University of Hohenheim, 2013)
Adequate access to good quality drinking water is an important prerequisite for the wellbeing and survival of people. Increasing competition over scarce freshwater resources with continuous quality deterioration is becoming a serious problem in many developing countries like Ethiopia, where the technical, socioeconomic and political conditions are impeding the proper utilization of the required resource. The concern of low quality water is either due to direct health impacts of poor quality drinking water or a reduction in the palatability of water for humans or animal consumption. The use of contaminated water in food production and/or processing can also be a considerable health concern for people. In rural households, water is used for multiple purposes including income generating activities such as livestock farming. Generally, the interactions among livestock, water and rural communities are very complex. Studies addressing the extent of water scarcity and quality problems in Ethiopia in such contexts are still limited. Therefore, a comprehensive assessment of water utilization by farmers and their livestock with respect to potential health and food safety impacts was carried out in two districts of Ethiopia. The specific objectives of the present study were to: (1) assess the constraints and challenges in meeting the water requirements of livestock kept by typical rural communities, (2) assess the utilization of water sources by livestock and people, (3) assess the suitability of water sources for human and livestock consumption based on microbiological and chemical quality indicators, (4) examine the microbiological quality of water at household levels and the potential health impacts, and (5) investigate the potential impacts of poor water quality on the microbiological safety of milk and milk products. The study was carried out in Lume and Siraro districts, both located in the Rift Valley of Ethiopia. Methodologically, the study encompassed different components: (1) a questionnaire survey complemented by focus group discussions with farmers, (2) assessments of the microbiological and chemical quality of water destined for human and/or livestock consumption, (3) microbiological assessments of milk and milk products produced and consumed by the local communities, and (4) a compilation of secondary data focusing on common human health problems in the districts. The questionnaire survey with 320 randomly selected farmers, the focus group discussions (n=16) and the compilation of secondary data were carried out from July to October 2010. Water samples were collected from sources and household containers from December 2010 to January 2011 and July to August 2011, corresponding to dry and wet seasons, respectively. During both sampling periods, a total of 25 water sources (sites where water was utilised or fetched for the purpose of human and/or livestock consumption) were assessed for microbiological and chemical quality parameters. A total of 126 and 109 water samples from household containers were collected in the dry and wet season, respectively. In addition, a total of 53 samples of milk and milk products were collected during the wet season and analyzed for E. coli contamination. Water samples collected from ground and surface water sources were analysed for total dissolved solids, pH, manganese, chromium, fluoride, E. coli and total coliforms. The assessed parameters were selected based on their importance to health or aesthetic aspects of water for human and/or livestock uses. The water samples from household containers were only analyzed for microbiological parameters. A summary of disease reports (July 2009-June 2010) was obtained from the Health Offices of the respective districts to assess the occurrence and impact of water-related human diseases. Descriptive statistics were calculated for the questionnaire survey data. Qualitative data collected in farmers’ group discussions were analyzed by organising the raised issues into logical categories. Mean ranks were calculated to compare the various constraints for livestock production mentioned by farmers. Non-parametric statistical tests were used to compare E. coli counts of water or milk between seasons and districts. The suitability of water sources for livestock and human consumption was evaluated by comparing the assessed quality parameters with recommended values. The study results showed that water sources intended for domestic and livestock uses were either ground water (hand-dug wells, boreholes) or surface water (river, dugout, surface runoff from roadsides). Challenges in the provision of water for livestock and/or people were associated with physical inaccessibility and high seasonal variation in the availability of water sources. Poor quality water for livestock drinking was rather a concern for communities in the proximity of urban settlements or industrial establishments. The mismanagement of harvested rainwater due to indiscriminate access of livestock to the sources was also found to pose high health risks on both livestock and people. Taking E. coli as an indicator of faecal pollution, the assessment of water samples showed that most of the surface water sources were contaminated with faecal materials and did not meet the WHO guidelines for drinking water quality. On the other hand, groundwater sources were microbiologically safe, but chemically contaminated with elements such as fluoride and manganese. In total, 76% of the water sources (n=25 points) assessed in this study failed to comply with WHO guidelines for human drinking water in both, the dry and the wet season for at least one parameter of health or aesthetic concern. Regarding pH, fluoride, manganese and chromium, 32% and 20% of the water sources were found unfit for livestock consumption in the dry and wet season, respectively. Another potential water-related health risk identified in this study was the considerable re-contamination of water after collection from sources. This can severely compromise the expected health benefits from the installation of improved water sources. For the overall assessed water samples from household containers, it was found that E. coli contamination was higher during the rainy season compared to the dry season. The microbiological assessment of milk produced and consumed in the study area showed a considerable contamination with E. coli. Although the correlation between the E. coli counts of milk and water was weak (Spearman’s rank correlation coefficient r=0.1), the recorded poor quality water still might have contributed to the low microbiological quality and safety of dairy products produced and consumed in the area. According to the secondary data collected from health offices, water-related human health problems potentially associated with the scarcity, poor quality and mismanagement of water sources were malaria, diarrhoea and gastro-intestinal parasites. Water-related livestock health problems were also reported by the farmers to be mainly associated with drinking water from stagnant dugouts and the industrially polluted Mojo River. In conclusion, the rural communities in the Rift Valley area of Ethiopia lack reliable access to safe water sources, with potential adverse health impacts. A possible priority of action that emanates from this study is a minimization of industrially associated water quality deterioration through the enforcement of existing environmental protection rules and regulations. Concurrently, awareness creation of the owners of the industries on the proper waste disposal mechanisms and environmental accountability should be targeted as one of the key aspects to alleviate the industry-related water pollution. On the other hand, in order to minimize the health risk associated with the mismanagement of rainwater harvesting systems, farmers should be technically supported by the local government in the proper design and management of the systems. Health education remains a necessary and crucial intervention to reduce the re-contamination of water. In this respect particularly women should be addressed, since they are customarily responsible for the collection and handling of water for domestic consumption.